Assessment of the in vitro metabolic stability of CEP-37440, a selective FAK/ALK inhibitor, in HLMs using fast UPLC–MS/MS method: in silico metabolic lability and DEREK alerts screening - Attwa, Mohamed W.; AlRabiah, Haitham; Abdelhameed, Ali S.; Kadi, Adnan A. (Frontiers in Chemistry, 2024)
CEP-37440 was synthesized and supplied by the research and development division of Teva Branded Pharmaceutical Products (West Chester, PA, USA). CEP-37440 represents a newly developed compound that exhibits selectivity inhibition of Focal Adhesion Kinase and Anaplastic Lymphoma Kinase FAK/ALK receptors, demonstrating novel characteristics as an orally active inhibitor. The simultaneous inhibition of ALK and FAK can effectively address resistance and enhance the therapeutic efficacy against tumors through a synergistic mechanism. The objective of this research was to create an LC-MS/MS method that is precise, efficient, environmentally friendly, and possesses a high level of sensitivity for the quantification of CEP-37440 in human liver microsomes (HLMs). The aforementioned approach was subsequently employed to evaluate the metabolic stability of CEP-37440 in HLMs in an in vitro setting. The validation procedures for the LC-MS/MS analytical method in the HLMs were performed following the bioanalytical method validation guidelines set out by the US-FDA. The AGREE program was utilized to assess the ecological impacts of the current LC-MS/MS methodology. The calibration curve linearity was seen in the range of 1-3000 ng/mL. The inter-day accuracy (% RE) exhibited a range of -2.33% to 3.22%, whilst the intra-day accuracy demonstrated a range of -4.33% to 1.39%. The inter-day precision (% RSD) exhibited a range of 0.38% to 3.60%, whilst the intra-day precision demonstrated a range of 0.16% to 6.28%. The determination of the in vitro half-life (t1/2) and moderate intrinsic clearance (Clint) of CEP-37440 yielded values of 23.24 minutes and 34.74 mL/min/kg, respectively. The current manuscript is considered the first analytical study for CEP-37440 quantification with the application to metabolic stability assessment. These results suggest that CEP-37440 can be categorized as a pharmaceutical agent with a moderate extraction ratio. Consequently, it is postulated that the administration of CEP-37440 to patients may not lead to the accrual of dosages within the human organs. According to in silico P450 metabolic and DEREK software, minor structural alterations to the ethanolamine moiety or substitution of the group in drug design have the potential to enhance the metabolic stability and safety profile of novel derivatives in comparison to CEP-37440.